2021
DOI: 10.7759/cureus.16341
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors for Metastasis in Newly Diagnosed Appendiceal Carcinoma

Abstract: BackgroundAppendiceal carcinoma has an insidious clinical presentation, and these tumors are rarely suspected prior to surgery, potentially leading to late diagnosis. The aim of this study is to investigate the prevalence of metastatic disease at initial presentation and potentially associated sociodemographic characteristics. MethodsPatients were identified from the Surveillance, Epidemiology, and End Results (SEER) program using the International Classification of Diseases for Oncology-3 (ICD-O-3) histology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In studies classifying GCA as local, regional, or metastatic disease, 51%–64% of cases were described as local ( 3 , 16 , 17 , 26 ). While metastases were found in only a relatively small proportion of cases in the registry studies (7%–18.7%) ( 3 , 11 , 12 , 16 20 , 23 , 26 ), stage IV disease was more common in retrospective studies and case series ( 7 , 37 , 39 , 44 , 49 , 52 , 58 , 73 ). It is likely that this finding is the result of referral bias, as higher rates of metastatic disease were reported by tertiary centres, with lower rates reported by district general hospitals and national registry studies ( 52 ).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In studies classifying GCA as local, regional, or metastatic disease, 51%–64% of cases were described as local ( 3 , 16 , 17 , 26 ). While metastases were found in only a relatively small proportion of cases in the registry studies (7%–18.7%) ( 3 , 11 , 12 , 16 20 , 23 , 26 ), stage IV disease was more common in retrospective studies and case series ( 7 , 37 , 39 , 44 , 49 , 52 , 58 , 73 ). It is likely that this finding is the result of referral bias, as higher rates of metastatic disease were reported by tertiary centres, with lower rates reported by district general hospitals and national registry studies ( 52 ).…”
Section: Resultsmentioning
confidence: 93%
“…Only one large registry study reported a median age out of this range at 43 years ( 23 ). GCA is more common in Caucasian patients, who account for 80-90% cases ( 3 , 11 , 12 , 14 20 , 25 , 26 ). There was no sex preponderance in most studies ( 3 , 11 , 12 , 14 , 16 , 18 , 20 , 23 , 25 , 26 ); however, this was variable in the smaller retrospective studies and case series.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations